Combining the formative with the summative: the development of a two-stage online test to encourage engagement and provide personal feedback in large classes - Susanne Voelkel (Association for Learning Technology, 2013)
The aim of this action research project was to improve student learning by encouraging more “time on task” and to improve self-assessment and feedback through the introduction of weekly online tests in a Year 2 lecture module in biological sciences. Initially voluntary online tests were offered to students and those who participated achieved higher exam marks than those who did not, but completion rate was low. Making the tests compulsory led to high completion rates, but class performance decreased, indicating that using the same assessment for formative and for summative purposes is not always beneficial for learning. Finally, these problems were resolved by introducing a two-stage approach: the first stage of each test was formative and provided prompt feedback. However, students had to achieve 80% to progress to the second summative stage of the test. The two-stage online tests led to significantly improved class performance. This novel test design ensures that students go through at least two attempts and therefore fully benefit from the learning opportunities presented by the formative stage. Two-stage online tests present the opportunity to provide regular feedback in large classes and to improve performance not only of good but also of “weak” students.